Effect of a Training Week on Heart Rate Variability in Elite Youth Rugby League Players - Edmonds, R. C.; Sinclair, W. H.; Leicht, A. S. (International Journal of Sports Medicine, 2013)
The aim of this study was to examine the influence of weekly training including a competitive game on heart rate (HR) variability (HRV). Youth players (n=9, age 17–20 years) were monitored during daily supine rest (10 min) and standing (8 min), 5 times over 8 days. Heart rate recordings were analysed for time domain, frequency (e. g. low frequency [LF], high frequency [HF]) domain and non-linear measures of HRV and compared using ANOVA or Friedman’s tests. Relationships between HRV and training workloads were examined via Spearman rank rho (ρ) correlation coefficients. Prior to a game, mean HR was significantly increased and remained elevated until 2 days post-game while parasympathetic modulations (HF) were significantly reduced (p<0.05). The supine to standing change in HRV was significantly reduced for up to 4 days post-game (LF/HF ratio, − 1.0±2.9 vs. − 3.0±1.9, p<0.05). These results confirm that prior to a game, players exhibited reduced parasympathetic and/or predominant sympathetic modulation with the game significantly reducing autonomic responses to standing for up to the following 4 days. Identification of day to day fluctuations in HRV may provide a helpful tool for monitoring player workload to maximise training and game performance.
Keywords: athlete; cardiac autonomic control; sport; performance; training workload